Pengaruh Penerapan Sistem Informasi Akuntansi, Standar Akuntansi Keuangan Dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Wajib Pajak Badan - Purnama, Hari (Universitas PGRI Yogyakarta, 2020)
This study aims to examine and analyze the effect of the application of accounting information systems, financial accounting standards and partial use of information technology on the quality of financial reports and to test and analyze the application of accounting information systems, financial accounting standards and the simultaneous use of information technology on the quality of financial reports.The variables of this study consist of independent and dependent variables. The independent variable of this research is the application of accounting information systems, financial accounting standards and the use of information technology, the dependent variable is the quality of financial statements. The population in this study is the corporate taxpayers in the city of Yogyakarta with a sample size of 100 respondents. The sampling technique was purposive sampling. The data collection method used a questionnaire. The analysis technique used is multiple linear regression with a significance level of 5%.The results showed that the application of accounting information systems, financial accounting standards and the use of information technology partially had a significant effect on the quality of financial reports. Simultaneously the application of accounting information systems, financial accounting standards and the use of information technology have a significant effect on the quality of financial reports. The effect of understanding the application of accounting information systems, financial accounting standards and the use of information technology on the quality of financial reports is 23.8%. The rest is influenced by other factors, namely 76.2%, which were not included in this study.